Event management : for tourism cultural and sporting events - Wagen, Lynn van der (Singapore, 2009)
The contents directly relate to competency units with industry examples providing application to match examination requirements as well as competency units. This Kit contains worksheets with multiple choice, short answer, worksheets, extension activities, assessment tasks, solutions, chapter review answers, mind map summaries and solutions.
Keywords: Special events- planning